2018
DOI: 10.1002/masy.201800111
|View full text |Cite
|
Sign up to set email alerts
|

H2S Sensing Material Based on Cotton Fabrics Modified with Polyaniline

Abstract: In this work, intelligent materials were developed from the cotton fabric modified with polyaniline (PAni). PAni was used in different oxidation states (Emeraldine Salt, Emeraldine, Leucoemeraldine and Pernigraniline Base). The obtained materials were tested as colorimetric hydrogen sulfide gas sensors. The intelligent fabrics were analyzed by Infrared Spectrometry (FTIR), X‐ray powder diffraction (XRD), Thermogravimetric Analysis (TGA), Energy Dispersive X‐Ray Spectroscopy (EDS), Optical Microscopy and Electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…The LoD reported was ≈1 ppm and the range was 1-20 ppm with a sensitivity of ≈70% at 20 ppm H 2 S. Almeida et al demonstrated PANI modified cotton fabrics for H 2 S measurement with a range of 1-1000 ppm. [185] All these PANI-based H 2 S sensors have their own advantages and disadvantages with respect to the intended application of food spoilage detection. Compared to the number of available PANI based NH 3 sensors, there are not as many PANI based H 2 S in the recent literature and therefore there are opportunities for one to investigate the possibilities of developing new PANI-based disposable flexible H 2 S sensors.…”
Section: Polyaniline-based Hydrogen Sulfide Sensorsmentioning
confidence: 99%
“…The LoD reported was ≈1 ppm and the range was 1-20 ppm with a sensitivity of ≈70% at 20 ppm H 2 S. Almeida et al demonstrated PANI modified cotton fabrics for H 2 S measurement with a range of 1-1000 ppm. [185] All these PANI-based H 2 S sensors have their own advantages and disadvantages with respect to the intended application of food spoilage detection. Compared to the number of available PANI based NH 3 sensors, there are not as many PANI based H 2 S in the recent literature and therefore there are opportunities for one to investigate the possibilities of developing new PANI-based disposable flexible H 2 S sensors.…”
Section: Polyaniline-based Hydrogen Sulfide Sensorsmentioning
confidence: 99%
“…Nowadays, the search for high‐performance, environmentally friendly, and low‐cost materials is constantly advancing. [ 7–114 ] According to Google Scholar, during the last decade (2010–2020), 1310000 articles were published in the area of high‐performance materials. They include high‐performance materials produced with polymers, with 12,5000 articles registered.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, we have contributed to the polyaniline field by producing new materials. These materials were used as pressure (35,76,99,124,145,160), gas (78,114) and magnetic (130) sensors. Over the years, we realized the need to improve the preparation of these materials, making them more Eco-friendly than the ordinary blends.…”
Section: Introductionmentioning
confidence: 99%